Emergency abdominoplasty following trauma - Suliman, Taifour M (Indian Journal of Plastic Surgery, 2006)
We report a case of modified abdominoplasty done on emergency basis to a 37 years old male with acute abdominal wall injury due to road traffic accident. We discuss the case and review the literature.
Keywords: Abdominoplasty; abdominal wall injury; emergency